Evaluating the visceral adiposity inflammatory index for enhanced stroke risk assessment - Qun Xiao; Aohan Xue; Weicheng Huang; Jian Yuan (Scientific Reports)
Abstract Stroke is a leading cause of global morbidity and mortality, with risk factors like visceral adiposity and inflammation playing significant roles. This study introduces the Visceral Adiposity Inflammatory Index (VAII), combining the Visceral Adiposity Index (VAI) and high-sensitivity C-reactive protein (CRP), to better predict stroke risk. Analyzing data from 8415 participants in the China Health and Retirement Longitudinal Study over 9 years, the study found that higher VAII levels were strongly associated with increased stroke incidence, with a hazard ratio of 1.91 for the highest quartile. VAII outperformed VAI and CRP alone in predictive accuracy, enhancing traditional risk models as shown by improved Net Reclassification Index and Integrated Discrimination Improvement Index. Furthermore, blood pressure and the triglyceride-glucose index were identified as mediators in the VAII-stroke relationship. These findings underscore VAII as a promising tool for stroke risk assessment, suggesting that public health interventions targeting VAII reduction could help mitigate stroke risk.